The Mediating Roles of Impulsiveness and Maladjustment in the Association of Psychological Resilience with Drug Addiction during Isolated Detoxification. (24th August 2021) - Zhuo, Ruirui; Chen, Zhencai; Shen, Xunbing; Yang, Hechen; Luo, Shuilian; Wu, Yuanqiang; Zhu, Yuxiang; Wu, Tingyun; Feng, Zhenjun; Cai, Hengbin
Abstract: Background: Studies have shown that psychological resilience is a key factor in drug rehabilitation. To explore the feasibility of developing psychological resilience as an addiction treatment intervention, it is essential to explore the role that it plays in drug addiction. Objectives: This study aimed to investigate the relationship between psychological resilience and drug addiction, as well as to examine the underlying mediational roles of maladjustment and impulsiveness in this association. Methods: We used a cross-sectional design that included a sample of 140 male drug addicts in compulsory isolation centers and used questionnaires and scales to ascertain their level of drug addiction, psychological resilience, maladjustment, impulsiveness, social support, and loneliness. Correlation and mediation effect analyses were performed to determine the roles of impulsiveness and maladjustment in the association of psychological resilience with drug addiction. Results: Psychological resilience was an inverse predictor of drug addiction. The results of the mediation effect analysis showed that maladjustment acted as a mediator between resilience and drug addiction and between impulsiveness and drug addiction. Furthermore, impulsiveness and maladjustment jointly mediated the relationship between psychological resilience and drug addiction. Conclusion: These findings highlight the importance of psychological resilience in maladjustment and impulsiveness for drug addicts and suggest that the role of psychological resilience in drug addiction needs to be further explored.